Diagnóstico diferencial del dolor orofacial i. Asociado a estructuras intracraneanas, extracraneanas y desórdenes sicogénicos - Rodolfo Acosta-Ortiz (Universidad de Antioquia, 2001)
Orofacial Pain (OFP) is a common problem among the general population and represents a condition that is potentially debilitating and deteriorating. The correct diagnosis is the principal base for an adequate management; in patients with DOF this may be a simple task or a very complex and frustrating experience for both, clinician and patient. However, the clinician's knowledge of all possible pain condition that can affect the orofacial region can facilitate the diagnostic process. It is important to emphasize that is very difficult to diagnose something unknown for the clinician and even though "common things occur commonly", it is not strange to find patients with "rare" pathologies, of low occurrence, which the clinician has forgotten or do not know. The fact that the clinician does not consider all these aspects during the clinical evaluation could easily guide him/her to be confused, which finally ends up in an inadequate diagnosis, wrong management, and possible devastating consequences for the patients. This is a series of three articles that have the purpose to present a literature review of the conditions that have been considered to establish the differential diagnosis of OFP. Pain associated to intracraneal structures (brain tumor headache), extracraneal estructures (teeth, eyes, and paranasal sinuses, among others) and psichogenic pain will be discussed in this first article.